New fluorine-containing hydrazones active against MDR-tuberculosis - Vavříková, Eva; Polanc, Slovenko; Kočevar, Marijan; Horváti, Kata; Bosze, Szilvia; Stolaříková, Jiřina; Vávrová, Kateřina; Vinšová, Jarmila (European journal of medicinal chemistry, 2011)
Several new fluorine-containing hydrazones were synthesized and screened for their in vitro antimycobacterial activity. Nine of these derivatives have shown a remarkable activity against MDR-TB strain with MIC 0.5 μg/mL and high value of selectivity index (SI). Compound 3h with the highest SI (1268.58) was used for stability evaluation with putative metabolites (ciprofloxacin and formylciprofloxacin) detection. Compound 3h was stable at pH 7.4 of aqueous buffer and rat plasma, in acidic buffers (at pH 3 and 5) slow decomposition was observed. Interestingly, no formylciprofloxacin was detected in the solution, and only slightly increased concentration of ciprofloxacin was observed instead. Trifluoromethyl hydrazones 3f and 3g exhibited the best activity also against two strains of Mycobacterium kansasii (MIC 1-4 μmol/L). All evaluated compounds were found to be non-cytotoxic.
Keywords: Tuberculosis, Multidrug-Resistant; Cell Line; Hydrazones; Antitubercular Agents; hydrazony; Microbial Sensitivity Tests; antituberkulotika; Mycobacterium; Mycobacterium kansasii; krysa rodu Rattus; Animals; lidé; Humans; zvířata; fluor; multirezistentní tuberkulóza; mikrobiální testy citlivosti; Rats; krevní plazma; buněčné linie; Fluorine; Plasma